THE EFFECT OF OMNI-CHANNEL CHANNELS ON CUSTOMER SATISFACTION IN RETAIL FASHION IN INDONESIA - Wahyuni, Nofi; Kurniawati, Kurniawati (Graduate Program of Universitas Tarumanagara, 2023)
The main purpose of this study is to analyze the effect pf Omni-Channel on E-Purchase Intention, P-Purchase Intention, Customer Experience and Customer Satisfaction and how brands use Omni-Channel to meet customer needs in retail fashion in Indonesia. This study uses primary data, the respondents in this study are people who have shopped fashion with online and offline channel. The model for this study used a non-probability sampling technique with purposeful sampling technique, therefore the sample used was 323 respondents. In addition, the analysis tool used in this study is structural equation modeling (Structural Equation Modeling-SEM) using the AMOS program. The empirical test results show that the Omni-Channel Capability has the greatest correlation value in influencing E-Purchase Intention, P-Purchase Intention, Behavior Intention to Customer Experience and Customer Satisfaction. The implication of this study shows that marketing managers must consider Omni-Channel strategy so that it can affect Consumer Satisfaction at fashion brand. For further research, it can also add and analyze additional factors that affect Re-Purchase Intention and Customer Loyalty.